1991
DOI: 10.1002/pros.2990180307
|View full text |Cite
|
Sign up to set email alerts
|

Histological changes in dunning prostate tumors and testes of rats treated with LH‐RH antagonist SB‐75

Abstract: Rats bearing Dunning R-3327 hormone-dependent prostate tumors were treated with LH-RH antagonist SB-75 in the form of microcapsules for sustained delivery administered every 3 weeks and which released 24, 48, 72 micrograms/day respectively. The effects were compared with those of microcapsules of the agonist D-Trp-6-LH-RH releasing 25 micrograms/day. Both types of LH-RH analogs significantly inhibited tumor growth over a period of treatment lasting 8 weeks. The effect of SB-75 was dose-dependent. The total inh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
16
0

Year Published

1991
1991
2002
2002

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 41 publications
1
16
0
Order By: Relevance
“…Mitotic and apoptotic cells were counted in 10 standard high-power microscopic fields containing, on the average, 400 cells, and their numbers per 1,000 cells were accepted as the mitotic and apoptotic indices, respectively. For demonstration of the nucleolar organizer region in tumor cell nuclei, the silver nucleolar organizer region method was used (27). The silver-stained black dots in 50 cells of each tumor were counted, and the silver nucleolar organizer region number per cell was calculated.…”
Section: Rna Extraction and Reverse Transcription (Rt)-pcrmentioning
confidence: 99%
“…Mitotic and apoptotic cells were counted in 10 standard high-power microscopic fields containing, on the average, 400 cells, and their numbers per 1,000 cells were accepted as the mitotic and apoptotic indices, respectively. For demonstration of the nucleolar organizer region in tumor cell nuclei, the silver nucleolar organizer region method was used (27). The silver-stained black dots in 50 cells of each tumor were counted, and the silver nucleolar organizer region number per cell was calculated.…”
Section: Rna Extraction and Reverse Transcription (Rt)-pcrmentioning
confidence: 99%
“…Mitotic and apoptotic cells were counted in 10 high-power fields, and their number per 1000 cells was calculated. For the demonstration of the nucleolar organizer region (NOR) in tumor cell nuclei, the argyrophilic NOR (AgNOR) method of Chiu et al (21) was used with little modification (22). The silver-stained black dots in 50 cells of each tumor were counted and the AgNOR number per cell was calculated.…”
mentioning
confidence: 99%
“…The extent of necrosis was measured on the slide containing the largest cross section of tumors, and the percentage area of necrosis was calculated by using an ocular net with 100 crossing points. All (16,20,22). …”
mentioning
confidence: 99%
“…Blockade of the pituitary LHRH receptors prevents stimulatory effects of native LHRH and results in rapid inhibition of the pituitary-gonadal axis; thus, testosterone suppression is immediate without the characteristic stimulatory phase for LHRH superagonists (Scheme 3). In addition, it has been reported that LHRH antagonists directly inhibit growth of numerous tumors, including mammary, pancreatic, and prostatic tumors, by binding to receptors localized on tumor cells [18][19][20][21].…”
Section: Methodsmentioning
confidence: 99%